Functional outcome of intertrochanteric fractures treated with trochanteric stabilizing plates - Shetty, Sunil H.; Nagori, Abdul Malik; Paneliya, Manan B.; Sharma, Vidur; Patil, Digvijay S.; Shetty, Aaishree (International Journal of Research in Orthopaedics, 2023)
Background: Intertrochanteric fractures account for significant percentage of health care costs and result in high rates of morbidity and mortality. Since higher rate of mortality and complications most fractures can be successfully treated with trochanteric stabilizing plates. This study was conducted to assess functional outcome in intertrochanteric fracture femur treated with trochanteric stabilizing plates and define ideal mode of fixation for such fractures. Trochanter stabilizing plate (TSP) is modular extension of dynamic hip screw (DHS) that is mounted on lateral femoral wall to stabilize greater trochanter. It provides the flexibility to achieve plate to bone apposition as well as axial compression or angular stability because of three screw fixations at the proximal fragment. TSF can provide a stress shield for the lateral trochanteric wall and prevent lateral migration of proximal fragments. Thus, TSF does not fail at the screw bone interface and provide a strong anchor in osteoporotic bone. The multiple locking screw holes of the TSF provide various options to tackle complex fracture pattern. It functions as an internalized external fixator and minimizes the pressure on the periosteum and encourages biological healing. Methods: A total of 30 subjects of intertrochanteric fractures undergoing treatment with trochanteric stabilizing plates were taken up for the study after informed consent. Results: Significant results were obtained using Harris hip score (HHS) at different postoperative follow up time intervals with good outcome and low complication rate. Conclusions: Trochanteric buttress plate creates biomechanically stable construct by incorporating the comminuted trochanter it restores the proximal femoral anatomy, ensuring anatomical reduction hence subsequently reduces limb length discrepancy. We thus conclude this is an effective technique and has excellent functional and radiological outcomes with minimal complication and early rehabilitation rates. As Intertrochanteric fractures of the hip is a very common condition affecting a large number of patients of variable demographics and racial background, a more widespread study is required for a more conclusive study.